Theoretical-Experimental Modal Analysis of a Flexible Rotor Based on the Jeffcott Model - Ruíz-Rodríguez, Javier; Morales-Hernández, Brian Farid; Sánchez-Acevedo, Heller Guillermo (Ingeniería, 2025)
Context: Rotating equipment that operates at high speeds or handles significant loads is designed based on the concept of flexible shafts. This is the case with turbines, compressors, and turbopumps, among others. The theoretical-experimental modal analysis of these shafts is crucial for ensuring a safe and efficient operation, as well as for identifying appropriate maintenance strategies. Method: In this work, we perform both theoretical and experimental modal analyses of an isotropic flexible rotor based on the Jeffcott model. The theoretical modal analysis is carried out using a numerical model with conditions similar to those of the experimental analysis. The results are compared using the modal assurance criterion (MAC). The validated numerical model enables the evaluation of eigenfrequencies and their associated modal shapes. Results: The first two bending natural modes of the flexible rotor were obtained from the theoretical and experimental modal analysis, and the mode shapes and natural frequencies were determined. The mode shapes were correlated, exhibiting a correlation value greater than 88%, thus validating the numerical model. Conclusions: This approach not only enhances the understanding of the shaft’s dynamic response but also contributes to improved decision-making during the design and operation stages of rotating systems in various industrial applications.